Isu-isu perundangan dalam pelaksanaan sistem kadaster berkoordinat di Semenanjung Malaysia - Md. Kasim, Mustafa (2008)
The cadastral system in Malaysia emphasizes on the lot dimension measurement align to ensure the adjoining lots can be given with an actual ownership. In line with the present technological development to increase the efficiency and effectiveness to the present system, as well as to cater to the consumer’s needs, this Coordinated Cadastral Systems (CCS) is being introduced. The concept of the system was first introduced in 1996 by the Department of Surveying and Mapping, which aims to improve the countries cadastral system, so that the efficiency and effectiveness of the deliveries system can be uphold. With the cooperation of the Faculty of Geoinformation Science and Engineering, University Technology Malaysia, a pilot project was proposed and implemented. The State of Malacca was chosen as the pilot project study area to implement this system. The objectives of the research are to study on the current cadastral system, implementation of CCS system includes legal boundaries and legal coordinates, hierarchy of boundary evidence and legalization issues about CCS system in Malaysia. Research methodology is based on the current situation system which has been practiced in the relating department using primary and secondary data. Due to the economic growth and the development of land, the current Digital Cadastre Database (DCDB) not enough capable to support the CCS system such as integrated and handshaking the other system, established PDUK-GIS ready, build 3D database of strata, stratum and marine?create Geographical Survey Record (GSRS) and to protect data component. The new DCDB named as National Digital Cadastral Database (NDCDB) should be created and clarified. A proper guide line is needed to ensure the system can be implemented properly. The study also indicated that coordinates is the important element in the CCS system because of the uniqueness and unambiguous. Through coordinates, the data such as bearings, lots and distances can be searched and accessed accurately. The result of the research had been found that the cadastral coordinates system must be legalized, survey regulation should be launched and NDCDB must be legalized. The findings and results would also no objection to its implementation and will be improved continuously. Hence, it is hoped that this system be implemented globally to all consumers.